Konfiguracijski prostori in topološka kompleksnost - Franc, Aleksandra (Obzornik za matematiko in fiziko, 2013)
We look at few examples of configuration spaces and introduce the notion of topological complexity. Finally, we use the famous Hairy Ball Theorem of Brouwer to construct explicit motion planning rules and determine the topological complexity of spheres.
Keywords: matematika; mathematics; topologija; topology; topološka kompleksnost; topological complexity; Fibrewise Lusternik-Schnirelmann category; Fibrewise Lusternik-Schnirelmannova kategorija